Microbial Contamination of Eye Drops in out Patient in Iraq - Raghad A. Razooki; Ebtihal N. Saeed; Hanan I. Omar Al-Deem (College of Pharmacy University of Baghdad, 2017)
Acontaminated ophthalmic solutions represent a potential cause of avoidable ocular infection. This study aimed to determine the magnitude and pattern of microbial contamination of eye drops in out patient at the department of ophthalmology, at Baghdad national hospital, Iraq. Fifty four vials from the out patient clinic were obtained for microbial examination after an average use of 2 weeks. The dropper tip and the residual eye drop were examined for contamination. The specimens were cultured, the number of colonies counted, the organisms identified. Eight (15%)  out of 54 analyzed vials were contaminated , most bacteria identified belonged to the normal commensal flora of the eye. Isolated contaminants were Staphylococcus auereus, Micrococcus , Neisseria catarrhalis, Gram negative Rods, Candida albicans, and Staph epidermidus.The dropper tip was more often contaminated (n=5) than the residual solution (n=2) and only one vial showed acontamination of both the drop and the tip (n=1) . Our data show acontamination rate of 15%, which is in the medium range of data puplished on the contamination of eye drops elsewhere (0.07% to 35.8%). Key words : Microbial Contamination, Eye Drops